Multilateral resistance to migration - Simone Bertoli; Jesús Fernández-Huertas Moraga (Institute for the Study of Labor (IZA), 2011)
The rate of migration observed between two countries does not depend solely on their relative attractiveness, but also on the one of alternative destinations. Following the trade literature, we term the influence exerted by other destinations on bilateral flows as Multilateral Resistance to Migration, and we show how it can be accounted for when estimating the determinants of migration flows in the context of a general individual random utility maximization model. We propose the use of the Common Correlated Effects estimator (Pesaran, 2006) and apply it to high-frequency data on the Spanish immigration boom between 1997 and 2009. Compared to more restrictive estimation strategies developed in the literature, the bias goes in the expected direction: we find a smaller effect of GDP per capita and a larger effect of migration policies on bilateral flows.
urn:nbn:de:101:1-201109297577
Keywords: F22; O15; J61; 330; international migration; economic determinants; migration policies; time-varying attractiveness; multiple destinations; Internationale Wanderung; Makroökonomischer Einfluss; Migrationspolitik; Spanien